2017
DOI: 10.1002/tie.21921
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating greater self‐confidence in African management research

Abstract: Although strategic management has taken root in many African organisations, much of the existing body of African management research offers little insight into the current state of knowledge and direction in terms of Africa finding its voice within the mainstream research.We draw on a review of the literature to develop a conceptual framework for classifying the contributions in African management research. The conceptual model captures the indigenous (intra-Africa) and inter-Africa dimension of macro-strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 109 publications
1
18
0
Order By: Relevance
“…German and Stroud (2007) in the fifth strand have attempted to comprehend the application of research and development in the light of typologies, lessons and consequences of approaches in learning. This stream is in accordance with the imperative to enhance research and development across the continent (Anyanwu, 2012;Chavula, 2010;African Development Bank, 2007), especially with regard to the lagging position of Africa in contribution to knowledge by means of scientific publications (Asongu & Nwachukwu, 2016a;Amankwah-Amoah, 2017).…”
Section: Intuition Theoretical Underpinnings and Ke Literaturesupporting
confidence: 54%
“…German and Stroud (2007) in the fifth strand have attempted to comprehend the application of research and development in the light of typologies, lessons and consequences of approaches in learning. This stream is in accordance with the imperative to enhance research and development across the continent (Anyanwu, 2012;Chavula, 2010;African Development Bank, 2007), especially with regard to the lagging position of Africa in contribution to knowledge by means of scientific publications (Asongu & Nwachukwu, 2016a;Amankwah-Amoah, 2017).…”
Section: Intuition Theoretical Underpinnings and Ke Literaturesupporting
confidence: 54%
“…In addition, in light of the growing technological trends and breakthroughs, it may be necessary for nations to update their regulatory and digital code of conducts in timely manners to keep pace with new practices. Beyond embracing a science‐led development agenda as advocated in Ghana by Kwame Nkrumah in the 1950s (see Amankwah‐Amoah, , ), nations lacking human capital can turn to the diaspora as a source of untapped talent. Given that most African countries have ineffective or non‐existing strategies to leverage the social, human, and financial capital of their diaspora to power economic development (Chand, ), diaspora‐country‐of‐origin knowledge‐exchange forums and conferencing might be useful in fostering positive knowledge diffusion.…”
Section: Discussionmentioning
confidence: 99%
“…It had been previously indicated that the overall development of behavioral traits, attitude, skills, and knowledge of employees influences a stoppage in cooperation towards the environment [24], which falls under the common umbrella of training and development. A previous study showed that green training helped in the preparation of different and multi-talented employees through the improvement of knowledge, competencies, and skills required for innovation and this improved the performance of an organization [25].…”
Section: The Impact Of Green Training On Green Environmental Performancementioning
confidence: 99%